Integrated transcriptome, small RNA, and degradome analysis to elucidate the regulation of rice seedling mesocotyl development during the passage from darkness to light - Yusong Lyu; Xiangjin Wei; Min Zhong; Shipeng Niu; Shakeel Ahmad; Gaoneng Shao; Guiai Jiao; Zhonghua Sheng; Lihong Xie; Shikai Hu; Yawen Wu; Shaoqing Tang; et al. (Crop Journal, 2020)
The mesocotyl, a structure located between the basal part of the seminal root and the coleoptile node of seedlings, contributes to pushing the shoot tip through the soil surface, a function that is essential for the uniform emergence of direct-seeded rice. Its elongation is inhibited by light and induced in darkness. This investigation of an indica rice (P25) with vigorous mesocotyl elongation was aimed at identifying the “omics” basis of its light-induced growth inhibition. A transcriptomic comparison between mesocotyl tissues that had developed in the dark and then been exposed to light identified many differentially expressed genes (DEGs) and differentially abundant microRNAs (miRNAs). Degradome sequencing analysis revealed 27 negative miRNA-target pairs. A co-expression regulatory network was constructed based on the miRNAs, their corresponding targets, and DEGs with a common Gene Ontology term. It suggested that auxin and light, probably antagonistically, affect mesocotyl elongation by regulating polyamine oxidase activity.